Epidemiological characteristics of live births with esophageal atresia in Sao Paulo State, Brazil, from 2005 to 2018 - Emilli Freitas Silvestri; Eduardo Jamil Farah Oliveira; Marcela Chiedde; Edige Felipe Sousa Santos; Mauricio Giusti Calderon (BMJ Publishing Group, 2023)
Background The estimated prevalence of esophageal atresia (EA) is 1 in 2500-4500 live births (LBs). Researchers have already identified risk factors, but the mechanisms are still unknown. The aim of this study is to identify EA prevalence trends and its risk factors in the São Paulo State (SPS) population database.Methods We conducted a population-based study using all EA cases identified by the Live Births Information System across 14 years (2005-2018) to estimate EA prevalence trends in recent years, stratified by maternal age and SPS geographical clusters. We calculated the prevalence trends, regression coefficient (β), annual percent change (APC), and 95% confidence interval (CI).Results We found 820 EA cases among 8,536,101 LBs with a prevalence of 1.0/10,000 LBs in SPS, Brazil. There was no significant difference in distribution by sex. Among all the cases, the majority (65%) were Caucasian; 51.8% were born at term; 43% had weight of ≥2500 g; 95.4% were singleton; and 73.4% of births were by cesarean section. From 2005 to 2018, there was an increasing trend of EA prevalence (APC=6.5%) with the highest APC of 12.2%. The highest EA prevalence rate (1.7/10,000 LB) was found in the group with maternal age of ≥35 years. No significant seasonal variation was found based on the conception month (p=0.061).Conclusions EA had an increasing prevalence trend in SPS, Brazil, in recent years, with the highest prevalence rate in the group with maternal age of ≥35 years. No seasonality was observed. This population-based study is the first to summarize the current epidemiology of EA in SPS LB.